2012
DOI: 10.1021/jp301342f
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase Total Oxidation of Benzene, Toluene, Ethylbenzene, and Xylenes Using Shape-Selective Manganese Oxide and Copper Manganese Oxide Catalysts

Abstract: Figure S1. Schematic diagram of the catalytic performance set-up for gas-phase VOC total oxidation. Relative Intensity (a.u.) 70 60 50 40 30 20 10

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
125
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 245 publications
(130 citation statements)
references
References 66 publications
2
125
0
3
Order By: Relevance
“…A major O 2 loss from both of the materials was observed (532 • C for UCT-1 and 570 • C for UCT-18-Cs) in the O 2 -TPD (Fig. 5C), which can be ascribed to the loss of lattice oxygen near the surface of the material [38].…”
Section: Metalmentioning
confidence: 94%
“…A major O 2 loss from both of the materials was observed (532 • C for UCT-1 and 570 • C for UCT-18-Cs) in the O 2 -TPD (Fig. 5C), which can be ascribed to the loss of lattice oxygen near the surface of the material [38].…”
Section: Metalmentioning
confidence: 94%
“…These organic compounds were chosen as model compounds to be used in this study due to their action as greenhouse gases and their toxic, carcinogenic and molecular characteristics (Wu et al, 2011;Genuino et al, 2012). The effect of the cobalt content on the textural properties of the catalysts and on the catalytic performance was also investigated.…”
Section: Brazilian Journal Of Chemical Engineeringmentioning
confidence: 99%
“…It has been found that less expensive materials such as Mn-oxide, Cu-oxide and Ni-oxide can also show substantially high activity towards oxidation of VOCs [16,[20][21][22][23][24][25]. There are some materials, which are generally known to be catalytically less reactive; however, there can be a drastic increase in the catalytic activity as the materials exist in the form of very thin film or nanoparticles less than 5 nm in diameter [11,13,15].…”
Section: Introductionmentioning
confidence: 99%